Arundinella setosa var. setosa (Poaceae): a new record for Andaman and Nicobar Islands, India - Lakra, R.; Kumari, P.; Mondal, S. (Rheedea, 2022)
Arundinella setosa Trin. var. setosa (Poaceae) is reported as a new addition to the grass flora of Andaman and Nicobar Islands. This adds a further species to the two species of Arundinella that have been enlisted in earlier reports from this region. A description, phenological and ecological notes, world distribution, photographic plates, and an identification key are provided.